2011
DOI: 10.1162/jocn_a_00051
|View full text |Cite
|
Sign up to set email alerts
|

Disrupting the Ventral Premotor Cortex Interferes with the Contribution of Action Observation to Use-dependent Plasticity

Abstract: Action observation (AO), observing another individual perform an action, has been implicated in several higher cognitive processes including forming basic motor memories. Previous work has shown that physical practice (PP) results in cortical motor representational changes, referred to as use-dependent plasticity (UDP), and that AO combined with PP potentiates UDP in both healthy adults and stroke patients. In humans, AO results in activation of the ventral premotor cortex (PMv), however, whether PMv activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…In our opinion the most plausible interpretation of this datum is that the actual joint displacement is causally involved in producing the MVA. This finding is supported by results in non-human primates, in the motor systems of which, the double coding of goals and movements is widespread [15][18]. Another interpretation that cannot be ruled out by the present data is that it is the somatosensory rather than the visual information that determines this component of the MVA.…”
Section: Discussionsupporting
confidence: 83%
“…In our opinion the most plausible interpretation of this datum is that the actual joint displacement is causally involved in producing the MVA. This finding is supported by results in non-human primates, in the motor systems of which, the double coding of goals and movements is widespread [15][18]. Another interpretation that cannot be ruled out by the present data is that it is the somatosensory rather than the visual information that determines this component of the MVA.…”
Section: Discussionsupporting
confidence: 83%
“…We hypothesise that this influence arises upstream from M1. It is well established that action observation activates the ventral premotor cortex (PMv) (Iacoboni et al, 1999), that the connections between PMv and M1 are enhanced with action observation (Koch et al, 2010), and that disruption of PMv with inhibitory rTMS can disrupt the contribution of action observation to use-dependent plasticity (Cantarero et al, 2011). Based on our findings, we speculate that action observation triggers a locally specific increase in functional connectivity between PMv and M1.…”
Section: Discussionsupporting
confidence: 67%
“…A previous study in healthy subjects reported that observing another person learn a novel task improves subsequent performance of the same task [126]. Moreover, data from a recent virtual lesion study using TMS further supports the hypothesis that action observation coupled with physical practice may enhance use-dependent plasticity through the mirror neuron system in healthy controls [131]. …”
Section: Integration Between Motor Learning and Multisensory Feedbackmentioning
confidence: 56%